TINGKAT KEPUASAN PELANGGAN TERHADAP KUALITAS PELAYANAN BRT TRANS TANGERANG PADA KORIDOR 2 - Dadang Suyadi; Winoto Hadi; Anita Susanti; Amalia Yasmin (LOGISTIK, 2021)
This study aims to measure the level of customer satisfaction with the perception of reality or performance of service quality provided by BRT Trans Tangerang in corridor 2. This Final Project was created using the following method is descriptive quantitative. The sample used to prepare this Final Project is amounted to 100 respondents, namely passengers of BRT Trans Tangerang on corridor 2. The results showed that the reality of the service from BRT Trans Tangerang corridor 2 was in a good criteria with an average values of 3,96 while customer expectations of reality/performance of BRT Trans Tangerang corridor 2 service are at a very high criterion with a total average values of 4,51. The results of the overall suitability analysis obtained a level of conformity of 87,6%, the values is still below 100%. This means that the overall service performance of BRT Trans Tangerang corridor 2 too it’s customers in terms of tangible, reliability, responsiveness, assurance, and empathy is very good but has not fully reached 100% in accordance with customer expectations or interests.